Real-time biofeedback of performance to reduce braking forces associated with running-related injury: An exploratory study - Napier, C.; MacLean, C. L.; Maurer, J.; Taunton, J. E.; Hunt, M. A. (Journal of Orthopaedic & Sports Physical Therapy, 2018)
Running-related injury (RRI) rates are high and may be associated with increased peak braking forces (PBF) and vertical loading rates. Gait retraining has been suggested by some experts to be an effective method to reduce loading parameters. Objectives: To investigate 1) whether PBF could be decreased following an 8-session gait retraining program among a group of female recreational runners and 2) the self-selected kinematic strategies to achieve this reduction. Methods: Twelve female recreational runners with high PBF (> 0.27 BW) completed an 8-session gait retraining program with real-time biofeedback of braking forces over the course of a half-marathon training program. Baseline and follow-up kinetics and kinematics were analysed with a repeated measures analysis of variance. Results: There was an average reduction of 15% in PBF (-0.04 BW; 95% CI: -0.07, -0.02; P=0.001; ES=0.62) accompanied by a 7% increase in step frequency (SF; 11.3 steps/min; 95% CI: 1.8, 20.9; P=0.024; ES=0.38) and 6% decrease in step length (SL; -5.5 cm; 95% CI: -9.9, -1.0; P=0.020; ES=0.40) from baseline to follow-up. Conclusion: The gait retraining program significantly reduced the PBF among a group of female recreational runners. This was achieved through a combination of increased SF and decreased SL. Furthermore, the modified gait pattern was incorporated into the runners` natural gait pattern by the completion of the program. Based on these results, the outlined gait retraining program should be further investigated to assess whether it may provide an effective injury prevention strategy for recreational runners.